2013
DOI: 10.1155/2013/691023
|View full text |Cite
|
Sign up to set email alerts
|

Ox-LDL Promotes Migration and Adhesion of Bone Marrow-Derived Mesenchymal Stem Cells via Regulation of MCP-1 Expression

Abstract: Bone marrow-derived mesenchymal stem cells (bmMSCs) are the most important cell source for stem cell transplant therapy. The migration capacity of MSCs is one of the determinants of the efficiency of MSC-based transplant therapy. Our recent study has shown that low concentrations of oxidized low-density lipoprotein (ox-LDL) can stimulate proliferation of bmMSCs. In this study, we investigated the effects of ox-LDL on bmMSC migration and adhesion, as well as the related mechanisms. Our results show that transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Previous studies showed that the number of circulating EPCs was inversely correlated with total cholesterol, LDL-cholesterol and ox-LDL levels [11,[58][59][60]. However, Zhang et al reported that the transmigration rates of BM mesenchymal stem cells (MSCs) and cell-cell adhesion between BM MSCs and MCs were significantly increased with ox-LDL treatment in a dose-and time-dependent manner [61]. Our previous [36] and present studies demonstrated that ox-LDL could significantly decrease both circulating MNCs and EPCs levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the number of circulating EPCs was inversely correlated with total cholesterol, LDL-cholesterol and ox-LDL levels [11,[58][59][60]. However, Zhang et al reported that the transmigration rates of BM mesenchymal stem cells (MSCs) and cell-cell adhesion between BM MSCs and MCs were significantly increased with ox-LDL treatment in a dose-and time-dependent manner [61]. Our previous [36] and present studies demonstrated that ox-LDL could significantly decrease both circulating MNCs and EPCs levels.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that ox‐LDL could activate ERK1/2 following short‐term (12‐hour) exposure . ERK1/2 are members of the mitogen‐activated protein kinase superfamily that are involved in cell proliferation, differentiation, migration, and apoptosis . Many studies have shown that the transformation of stem cells to cardiomyocytes involved the activation of ERK1/2 in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 54%
“…In a recent study, we found that ox‐LDL could stimulate proliferation of BM‐MSCs via activation of LOX‐1 receptor . We also observed that ox‐LDL could activate ERK1/2 following short‐term (12‐hour) exposure .…”
Section: Discussionmentioning
confidence: 63%
“…The growth factors FGF2 and VEGF have also been shown to promote the proliferation, migration and adhesion of human periodontal ligament stem cells in vitro (Zhang et al 2013b). Ox-LDL has also been shown to increase the migration and adhesive behaviour of BMSCs via upregulation of MCP-1 expression (Zhang et al 2013a). Studies have also demonstrated that the mRNA expression of CXCR4, FGF2, MCP-1 and SDF-1 is upregulated in response to HDACis (TSA 20 nmol L À1 or VPA 1 mmol L À1 ) in hDPSCs, and subsequently, the Western blot results also confirmed that TSA (20 nmol L À1 ) or VPA (1 mmol L À1 ) increased the expression of chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…The medium was changed every three days. hDPSCs were characterized by flow cytometry and analysis of multiple lineage differentiation potential as described previously (He et al 2013, Zhang et al 2013a. Cells between passages 2 and 5 were used in all experimentation.…”
Section: Cell Culturementioning
confidence: 99%